Interstitial High-Dose-Rate Brachytherapy Combined with External Beam Radiation Therapy for Dose Escalation in the Primary Treatment of Locally Advanced, Non-Resectable Superior Sulcus (Pancoast) Tumors: Results of a Monocentric Retrospective Study - Neu, Maria; Kahl, Klaus Henning; Körner, Melina; Walter, Renate; Raab, Stephan; Jehs, Bertram; Käsmann, Lukas; Strnad, Vratislav; Stüben, Georg; Balagiannis, Nikolaos (Journal of Clinical Medicine, 2024)
Objectives: To analyze the results of interstitial (IRT) high-dose-rate (HDR) brachytherapy (BT) in the primary treatment of patients with unresectable superior sulcus tumors (SST) combined with external beam radiotherapy (EBRT). Methods: Between 2013 and 2023, seven patients with unresectable SST were treated with combined BT and EBRT with or without concomitant chemotherapy. The patients’ median age was 64 years (range, 49–79 years) and median tumor volume was 146.8 cm3 (range, 29.3–242.3 cm3). A median BT dose of 8 Gray (Gy) (range, 5–10 Gy) was prescribed and delivered in a single fraction. A median EBRT dose of 54 Gy (range, 30–59 Gy) was prescribed and administered normofractionated (single dose: 1.8 Gy). Results: We report the results of seven patients with SST treated with combined BT and EBRT and followed for a median of 38 months. The overall clinical response rate was 83.33% with five out of six patients achieving local control, while one out of six (16.66%) showed local and general progression. No deaths were attributed to the treatment itself; rather, one patient died during the course of therapy as a result of systemic progression. The most common radiation-related adverse events were grade I–II fatigue and mild paresthesia. No severe toxicity (CTCAE ≥ III°) was observed with interstitial high-dose-rate (HDR) BT combined with EBRT. Conclusions: For patients with unresectable superior sulcus tumors, interstitial HDR BT in combination with EBRT is a feasible treatment option that offers the potential for local control and long-term survival. The findings of this study should be validated in a larger patient cohort.
CRIS-Team Scopus Importer:2025-02-04
Keywords: combined with EBRT; dose escalation; high-dose-rate; interstitial brachytherapy; locally advanced superior sulcus tumor; unresectable pancoast tumor